Organization of frame-monolithic works by various methods, determining the dynamics of investment - Tugaі, А. A.; Zelenkov, A. Yu. (Ways to Improve Construction Efficiency, 2020)
Construction is a complex system whose parameter values are constantly changing over time and depend on a huge number of factors. Successful completion of a construction project is to achieve the set goals: completion of construction on time, completion of planned workloads, optimal resource allocation, achievement of quality construction products. One of the most important technical and economic indicators of organizational and technological design is the duration of construction. Without its definition, it is impossible to correctly determine the cost of construction, to generate cash flow for the investment period of a construction project, to evaluate its effectiveness. The work is devoted to the organization of frame monolithic works of complexes by different methods, to determine the difference in cost, duration and dynamics of investments, which should be taken into account to the investor. Consideration was given to the construction of a monolithic frame of the house with the use of construction machines and mechanisms. - streaming method, and streaming optimized to eliminate downtime by adjusting construction time; - the parallel method with the greater use of resources; - the method is combined (parallel-sequential); is a sequential method. Functions defined: - cost dependence on the time of general complex construction; - the cost dependence of the time of individual work in the flow with downtime. One of the main tasks was to determine the optimal duration works for the investor, because the type of organization affects the following indicators: - duration; - cost; - dynamics of investments. Housing is one of the most important areas that determine the economic stability and economic growth of the country, requiring significant and long-term financial investment. That is why the organization of effective management of innovative investment activity in housing construction is a task of particular importance. However, the development of the housing market is hampered by the following factors: inefficient ways of managing construction projects, low level of mobility of economic flows in construction, lack of qualified specialists and participants in the investment construction process. Therefore, the development and implementation of effective ways of managing investment is an important task today.